Pilot study on the dynamic interactions between cardiac activity and corneal biomechanics during eye movements - Shahiri, Mohammadali; Kasprzak, Henryk; Asejczyk, Magdalena (Frontiers in Medicine, 2024)
The study examines the relationship between ocular rotations and cardiovascular functions through detailed biomechanical analysis. The study documents specific patterns of ocular movements and their synchronization with cardiovascular activity, highlighting significant correlations. These findings provide a basis for understanding the opto-biomechanical interplay between ocular and cardiovascular dynamics. Methods: Authors employed a customdesigned prototype, integrating a camera and numerical pulse oximeter, to analyze the right eyeballs of participants. The corneal surface reflections were recorded, along with concurrent blood pulsation (BP) signal acquisition. Numerical analysis helped determine the reflection positions and orientations to study eye movements and corneal deformations. Time and frequency domain analyses, including coherence functions, were utilized. Results: Significant correlations were found between variations in corneal curvature, selected Fixational eye movements (FEM) parameters, and Pulsatile ocular blood flow (POBF), revealing synchronized expansions of the corneal surfaces with cardiovascular activity. Furthermore, FEM displayed spectral correlations with BP, indicating an interrelation between ocular rotations and cardiovascular functions. Conclusions: These findings reveal the complex interactions between the cornea and Pulsatile Ocular Blood Flow (POBF), as well as between Fixational Eye Movements (FEM) and POBF. While the influence of POBF on both corneal dynamics and FEM is clear, further research is necessary to directly link corneal dynamics and FEM. These insights hold potential for non-invasive diagnostic applications and provide a deeper understanding of ocular biomechanics.